Simultaneous involvement of 11q23 translocation resulting in chimeric MLL-AFF1 and a second translocation [t (9;21) (p13; p11.2)] in an infant acute lymphoblastic leukemia patient at relapse: A case report. Issue 21 (May 2018) - Liu, Guangming; Lu, Xianglan; Kim, Young Mi; Wang, Xianfu; Li, Shibo; Liu, Yuanyuan
Abstract: Rationale: Three-way translocations occasionally occur in MLL-AFF1 fusion and other fusion gene. However, the complex chromosomal rearrangements in the study were the first report. Patient concerns: We present novel cryptic and complex chromosomal rearrangements [der (21) t (9; 21) (p13; p11.2)] in an infant patient with relapsed acute lymphoblastic leukemia (ALL). Diagnoses: The diagnosis was based on morphologic, cytochemical, and immunophenotypic criteria proposed by the French-American-British Committee, and karyotype, fluorescence in situ hybridization, array comparative genomic hybridization. Interventions: The patient was given chemotherapy with standard protocol for ALL. Outcomes: The patient had unfavorable prognostic outcome based on the cytogenetic and molecular cytogenetic markers. After short remission, the patient relapsed. Lessons: MLL-AFF1, resulting from t(4;11)(q21;q23), is regarded as the hallmark of infant t(4;11) pre-B/mixed B-ALL. It is associated with a dismal prognosis and the multiple-way translocation involving chromosomes 4, 11 and 11 may function as an enhancer.